SEASONAL CHANGES IN RESERVE SUBSTANCES OF HERBACEOUS PFRENNIALS IN THE ALPINE ZONE OF MT. FUJI (14th Symposium on Polar Biology) - カナイ, タエコ; マスザワ, タケヒロ; KANAI, Taeko; MASUZAWA, Takehiro (National Institute of Polar Research, 1993)
P(論文) The seasonal changes in soluble carbohydrates in rhizomes were measured for six species of herbaceous perennials growing in the gravelly habitats immediately above the timberline of Mt. Fuji. Arabis serrata and Polygonum weyrichii, the first colonizing species on newly exposed soil, used skillfully the reserve substances to adapt to the severe environment. Polygonum cuspidatum, Hedysarum vicioides and Astragalus membranaceus, second appearing species, accumulated a large amount of reserve substances in autumn due to their longer growing season. For Saussrea triptera, growing on the forest floor, the shoot growth slightly depended upon the reserve substances. Thus the respective species had different manners of using reserve substances corresponding to their environments. departmental bulletin paper